HIV-Infected Children Have Elevated Levels of PD-1+ Memory CD4 T Cells With Low Proliferative Capacity and High Inflammatory Cytokine Effector Functions. (26th July 2017) - Foldi, Julia; Kozhaya, Lina; McCarty, Bret; Mwamzuka, Mussa; Marshed, Fatma; Ilmet, Tiina; Kilberg, Max; Kravietz, Adam; Ahmed, Aabid; Borkowsky, William; Unutmaz, Derya; Khaitan, Alka
Summary: HIV-infected children have increased frequencies of PD-1 + memory CD4 T cells that correlate with HIV disease progression and fail to normalize with treatment. These cells have low proliferative capacity, preferentially secrete proinflammatory cytokines, and are unresponsive to PD-1 blockade. Abstract: Background: During human immunodeficiency virus (HIV) disease, chronic immune activation leads to T-cell exhaustion. PD-1 identifies "exhausted" CD8 T cells with impaired HIV-specific effector functions, but its role on CD4 T cells and in HIV-infected children is poorly understood. Methods: In a Kenyan cohort of vertically HIV-infected children, we measured PD-1 + CD4 T-cell frequencies and phenotype by flow cytometry and their correlation with HIV disease progression and immune activation. Second, in vitro CD4 T-cell proliferative and cytokine responses to HIV-specific and -nonspecific stimuli were assessed with and without PD-1 blockade. Results: HIV-infected children have increased frequencies of PD-1 + memory CD4 T cells that fail to normalize with antiretroviral treatment. These cells are comprised of central and effector memory subsets and correlate with HIV disease progression, measured by viral load, CD4 percentage, CD4:CD8 T-cell ratio, and immune activation. Last, PD-1 + CD4 T cells predict impaired proliferative potential yet preferentially secrete the Th1 and Th17 cytokines interferon-γ and interleukin 17A, and are unresponsive to in vitro PD-1 blockade. Conclusions: This study highlights differences in PD-1 + CD4 T-cell memory phenotype and response to blockade between HIV-infected children and adults, with implications for potential immune checkpoint therapies.